Deciphering the Role of Noncovalent Interactions in the Conformations of Dibenzo‐1, 5‐dichalcogenocines. Issue 4 (1st February 2022) - Weiss, Robin; Cornaton, Yann; Khartabil, Hassan; Groslambert, Loïc; Hénon, Eric; Pale, Patrick; Djukic, Jean‐Pierre; Mamane, Victor
Abstract: This work reports a combined experimental and theoretical study on the new dibenzo‐1, 5‐ditellurocine 2‐Te in order to get an overview on the parameters controlling conformational change and to explain the differences with sulfur and selenium analogues. The preference of the boat conformer over the chair one is revealed by DFT calculations. For 2‐Te, a ΔG value of about 3 kJ/mol was calculated, close to the value measured by NMR (5 kJ/mol). However, DFT calculations with implicit solvation effects could not clearly establish the presence of an intramolecular Te…HC noncovalent interaction (NCI), as observed in the solid state. The Independent Gradient Model (IGM) methodology discloses an existent but probably not sufficiently discriminating Te…HC NCI. It also confirms that van der Waals interactions between phenyl rings is a source of stabilization of the boat conformer. Furthermore, electrostatic potential analysis suggests that chalcogen bonds between Te σ‐holes and solvent might play an important role. Abstract : Insertion of tellurium atoms in the dibenzocyclooctadiene framework induced higher stability of the boat conformer, with an activation energy for the boat to chair conformational change of 78 kJ/mol. Besides the more stabilizing π‐π stacking interactions between the benzene rings in the boat conformation, other noncovalent interactions such as chalcogen bonds with the surrounding solvent molecules might explain the observed results.